Indonesia's Free Nutritious Meal Program Draws Positive Attention at UN Headquarters in Geneva - Montolalu Joshua, Verly (Jurnal Indonesia Sosial Sains, 2026)
Child nutrition fulfillment programs are an important issue in global development, especially in developing countries that are still facing the problem of inequality of access to nutritious food. One of the approaches that is widely applied is the school feeding program as an effort to improve children's health, welfare, and educational quality. Indonesia implements this policy through the Free Nutritious Eating Program (MBG) which also received positive attention in international forums at the United Nations (UN) headquarters in Geneva. This research aims to analyze the school feeding program policy through the MBG Program and examine the social and cultural implications it causes. The research uses a descriptive qualitative approach with data collection techniques through documentation studies, indirect observations of seminar materials, and literature studies from relevant scientific sources. Data analysis is carried out through data reduction, descriptive presentation, and systematic conclusion drawing by triangulating sources. The results of the study show that the MBG Program has a strategic role in improving children's nutritional status, supporting the learning process, and becoming a long-term investment in human resource development. In addition, this program also contributes to strengthening the national food system through the use of local food and has implications for the formation of community consumption culture. However, the implementation of the program still faces challenges in distribution, nutrition quality monitoring, and coordination between institutions. Thus, the MBG Program embodies health, education, food policy, and cultural identity in Indonesia and Southeast Asia.